The Influence of Learning Models on Students' Floor Exercise Learning Outcomes and Body Fitness - Ni Putu Diah Yeni Rahayu; I Gusti Lanang Agung Parwata; I Ketut Iwan Swadesi (UNIB Press, 2024)
Physical Education, Sports and Health are important components of overall education. The goal is to develop various aspects of the individual, including physical fitness, motor skills, critical thinking skills, social skills, argumentative skills, emotional stability, moral integrity, healthy lifestyles, and awareness of the importance of a clean environment. Learning gymnastics is one of the physical education materials for sports and health that experiences many obstacles. Not yet optimal and very limited facilities and infrastructure are the causes of less effective physical education learning, especially floor exercise. Gymnastics is one of the PJOK materials that must be provided in schools, especially elementary schools. Currently, many types of exercise have emerged, such as morning exercise, physical fitness exercise, and other educational exercises, each exercise has its own movement characteristics. Learning gymnastics for elementary school children is a tool to achieve comprehensive development which includes mental, physical, social and emotional. Gymnastics learning, especially artistic gymnastics, is the material in PJOK learning that faces the most obstacles, including facilities and infrastructure for learning purposes which are expensive, the risk of injury is quite high, and is considered scary for the majority of students, therefore as a teacher you must try to make learning The gymnastics is packaged in an interesting way so that students will like it and so that students are no longer afraid of taking part in gymnastics lessons.